2007
DOI: 10.2186/prp.6.272
|View full text |Cite
|
Sign up to set email alerts
|

A Relation Between the Piezoelectric Pulse Transducer Waveforms and Food Bolus Passage during Pharyngeal Phase of Swallow

Abstract: A portable device to measure laryngeal movements was developed with a Piezoelectric Pulse Transducer. Simultaneous recordings of the laryngeal movements, EMG, and VF elucidated the PPT waveforms and could detect bolus passage during the pharyngeal phase of swallow. This portable system has the possibility to measure the dynamic state of swallowing without VF. AbstractPurpose: Since a Piezoelectric Pulse Transducer (PPT) detects finger peripheral pulse-waves, the PPT has already been used to simply record the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 3 publications
2
12
0
Order By: Relevance
“…In a previous study [3] analysing simultaneously collected sSH EMG and piezoelectric data, the authors documented that a large positive deflection in their piezoelectric record corresponded to laryngeal downward movement. Our present study revealed a very similar positive deflection ('P 3 ' in figure 2), and we also observed the last component of the intsSH EMG in all five subjects, but similar previous studies have made little mention of this component [3][4][5]7,9,10]. This disparity may be due to methodological differences, such as subtle differences in the kind and placement of electrodes, that could alter the sEMG that is recorded.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In a previous study [3] analysing simultaneously collected sSH EMG and piezoelectric data, the authors documented that a large positive deflection in their piezoelectric record corresponded to laryngeal downward movement. Our present study revealed a very similar positive deflection ('P 3 ' in figure 2), and we also observed the last component of the intsSH EMG in all five subjects, but similar previous studies have made little mention of this component [3][4][5]7,9,10]. This disparity may be due to methodological differences, such as subtle differences in the kind and placement of electrodes, that could alter the sEMG that is recorded.…”
Section: Discussionsupporting
confidence: 87%
“…In one such study [3], for example, the authors investigated the relationship over time between the PES trajectory and surface electromyograms (sEMGs) of the submental and cricopharyngeous muscles during the oropharyngeal swallowing of liquid and solid test foods. Another study assessed the pharyngeal and esophageal transit of a bolus videofluorographically and found that characteristic videofluorographic features of the swallow (such as the pharyngeal transit time) correlated well with key features of the simultaneously recorded PES trajectory [4]. These studies suggest that PESs are suitable and useful in the research and clinical fields of swallowing, especially because they are readily available and do not involve exposure to radiation.…”
Section: Introductionmentioning
confidence: 92%
“…Recently, some other researchers even took advantage of VF and videoendoscopy (VE) to observe the temporal aspects of swallowing [27], [28]. They successfully recorded the thyroid cartilage trajectory over time and related pharyngeal swallowing events, such as epiglottis activity and laryngeal closure.…”
Section: Introductionmentioning
confidence: 99%
“…This provides important information about the timing of swallowing; see e.g. [1][2][3][4][5]. Moreover, the piezoelectric sensor, when attached to the chest, detects the respiratory movement during sleeping and is valuable for monitoring respiration in the clinic; see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we evaluated the applicability of piezoelectric sensors for studying speech by attaching a piezoelectric sensor to the front of the neck. As a control, we also recorded the electrical potential changes that occur during swallowing, as reported previously [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%